Loading of Oregano Oil in Natural Nanogel and Preliminary Studies on Its Antiviral Activity on Betacoronavirus 1 - Lyubomira Radeva; Maya M. Zaharieva; Sevda Naydenska; Pelagia Foka; Erini Karamichali; Efthymia Ioanna Koufogeorgou; Urania Georgopoulou; Stanislav Philipov; Alexander Kroumov; Hristo Najdenski; Ivanka Spassova; Daniela Kovacheva; et al. (Molecules)
Oregano oil was successfully encapsulated into chitosan–albumin nanogel via emulsification and electrostatic gelation. The system was characterized with a mean diameter around 26 nm, narrow size distribution (PDI = 0.242) and approximately 40% encapsulation efficiency. The incorporation of the oil into the nanogel was confirmed by XRD and FTIR analyses, and the dissolution of the oil was enhanced after the encapsulation. Furthermore, the treatment of Betacoronavirus 1 infected bovine kidney MDBK cells with the oregano oil-loaded nanogel (25 µg/mL) showed more than 50% protection against the infection, as compared to the non-treated virus infected control. The cytopathic effect (CPE) of the virus was inhibited in a concentration-dependent manner. The system inhibited the virus replication, resulting in a decrease of the viral particles by more than half, as shown by the cytotoxicity and CPE assays. The virus titer in treated and non-treated samples was determined by digital droplet PCR and revealed Δ3 log diminishment of the virus particles in samples treated with 25 µg/mL encapsulated oregano oil. This study is a basis for further investigations on the pharmacodynamics of the nanogel and its possible combinations with clinically applied chemotherapeutics.